2010
DOI: 10.1063/1.3392918
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and Raman studies of YNbO4 phosphors doped by Eu3+, Ga3+, and Al3+

Abstract: Efficient phosphors based on YNbO4 and doped by Eu3+, Ga3+, and Al3+ were synthesized with different fluxes under different thermal conditions and investigated under x-ray excitation and Raman spectroscopy. The samples codoped by Al3+ and Ga3+ show higher intensity under x-ray excitation in comparison with YNbO4:Eu3+ phosphors. The model of redistribution energy transfer from D51 level to F7J is proposed. Monoclinic fergusonite crystal structure and excellent luminescent properties under x-ray excitation allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 18 publications
3
13
0
5
Order By: Relevance
“…In view of the analysis of Raman vibration mode on scheelite type molybdate by Hanuza, [22] the specific vibration mode is shown in the following type:…”
Section: Characterizationmentioning
confidence: 99%
“…In view of the analysis of Raman vibration mode on scheelite type molybdate by Hanuza, [22] the specific vibration mode is shown in the following type:…”
Section: Characterizationmentioning
confidence: 99%
“…The photoluminescence properties of YNbO 4 activated by the ions Eu 3+ , Sm 3+ , and Er 3+ etc. have been reported [9,10]. Recently, Sung et al reported that the co-doping of Gd 3+ and Eu 3+ on the YNbO 4 phosphor dramatically enhances the luminance intensity due to the energy migration process like Gd 3+ !…”
Section: Introductionmentioning
confidence: 97%
“…Ниобат иттрия, активированный редкими землями, является перспективным радиационно-стойким сцинтиллятором, в частности рентгенолюминофором. Такие материалы могут использоваться в медицинской и промышленной рентгенографии [1,2]. Ниобат иттрия обладает высокой плотностью, что немаловажно при поглощении и преобразовании ионизирующего излучения в видимый свет, не гигроскопичен, а также обладает высокой радиационной и химической стойкостью.…”
Section: Introductionunclassified